Production of a monoclonal antibody against serum immunoglobulin M of South American camelids and assessment of its suitability in two immunoassays. (September 2014) - Friedrich, Adrián; Ledesma, Martín; Landone, Ignacio; Ferrari, Alejandro; Leoni, Juliana
A monoclonal antibody (mAb) was produced against immunoglobulin M (IgM) of South American camelids. A single radial immunodiffusion (SRID) assay and a competitive enzyme-linked immunosorbent assay (ELISA) were developed to measure IgM in serum samples. Isotype and specificity of the mAb were assessed. The performance of the SRID assay was preliminarily evaluated in terms of working range, plate stability over a 4-week period, and initial intra- and interassay variation. The concentration of IgM was determined in 55 samples by SRID assay and ELISA, and results were not significantly different by t -test (0.64 ± 0.19 mg/ml for the SRID assay, and 0.58 ± 0.24 mg/ml for ELISA; P = 0.1489). The mAb was shown to be stable over the 4-week evaluation period, and the SRID assay was reproducible when tested in triplicate for intra-assay variability and in quadruplicate for interassay variability, with a percentage coefficient of variation of less than or equal to 5%. Also, the SRID assay proved to be sensitive enough to measure IgM levels in undiluted serum samples, and had a good correlation with ELISA. The current study is intended to submit a preliminary report of a mAb against IgM of South American camelids, and suggest the future potential of the mAb developed for diagnostic application, including use in the SRID assay.